SISTEM INFORMASI UNIT KEGIATAN MAHASISWA DAN HIMPUNAN MAHASISWA JURUSAN POLITEKNIK NEGERI FAKFAK - Ardhyansyah Mualo; Hasan Basri; La Ode Syaiful Djamani (JURNAL ILMIAH INFORMATIKA, 2023)
Today's information systems are inseparable because they demand a company to create an integrated system that allows others to access the information they need from the company. The Student Activity Unit or UKM organization and the Departmental Student Association (HMJ) are two that are affected, making it simpler for students to obtain information, which is one of the most crucial requirements that must be met. Numerous student organizations are supervised by the Fakfak State Polytechnic and are grouped under the Student Activity Unit (UKM). Student activity units and major student associations at the Fakfak State Polytechnic currently do not have an integrated information system that explains management profiles, vision and mission, and work programs. This has an impact on the lack of information obtained by students and the public regarding UKM and HMJ at the Fakfak State Polytechnic. Therefore, efforts are needed to build and improve an information exchange system in the form of a website-based application for student activity units and departmental student associations that can manage information from each organization in an integrated manner to be able to overcome these problems. The information system that will be built and developed is a web-based application that makes it easier for users to access information and also acts as a promotional medium.